The turnover of jobs and workers in a deep recession: Evidence from the Finnish business sector - Pekka Ilmakunnas; Mika Maliranta (The Research Institute of the Finnish Economy (ETLA), 2001)
Job and worker flows in the Finnish business sector are studied during a deep recession in the early 1990s. The data set, Employment Statistics, covers effectively the whole work force. The gross job and worker flow rates are fairly high. Much of the adjustment of labor input has happened through a reduced hiring rate rather than through an increased separation rate. However, during the recession the group of declining plants included more and larger plants than before, which led to reduced employment. Excess worker turnover (churning) and excess job reallocation have dropped during the recession. There is no strong evidence of the countercyclicality of job reallocation. The flows are calculated both for the whole business sector, and for seven main industries. Services have clearly higher flow rates than manufacturing, but the cyclical changes in the flows are fairly similar in all industries. To test the sensitivity of the results to data sources, job flows are calculated also using Business Register and Industrial Statistics. – – Tutkimuksessa tarkastellaan työpaikka- ja työntekijävirtoja Suomen yrityssektorilla 1990-luvun alun syvän laman aikana. Aineistona käytetään työssäkäyntitilaston yksilöaineistoa, joka kattaa käytännössä ko. sektorin koko työvoiman. Työpaikkojen ja työntekijöiden bruttovirrat ovat suuria. Suuri osa työpanoksen sopeutuksesta on tapahtunut alentuneen työntekijöiden sisäänvirtausasteen kautta eikä niinkään nousseen ulos-virtausasteen kautta. Toisaalta laman aikana supistuvien toimipaikkojen ryhmään kuului enemmän ja suurempia toimipaikkoja, mikä johti työllisyyden alenemiseen. Työntekijöiden ylimääräinen vaihtuvuus (kirnuaminen) ja työpaikkojen ylimääräinen uudelleenallokaatio ovat alentuneet laman aikana. Tulokset eivät anna vahvaa tukea hypoteesille työpaikkojen uudelleenallokaation vastasyklisyydestä. Virrat on laskettu koko yrityssektorille ja seitsemälle päätoimialalle. Palvelualoilla virtojen asteet ovat selvästi korkeammat kuin teollisuudessa, mutta niiden suhdannevaihtelu on melko samanlaista kaikilla toimialoilla. Aineston vaikutuksia tuloksiin tutkitaan laskemalla työpaikkavirrat myös yritysrekisterin toimipaikka-aineistosta ja teollisuustilastosta.
Keywords: J23; J63; 330; job creation; job destruction; hiring; separation; churning; job reallocation; Beschäftigung; Arbeitsnachfrage; Kündigung; Konjunktur; Arbeitsmobilität; Finnland